Democratization of Public Investment in Chile. The Case of Participatory Budgeting in Los Ríos Region - Montecinos, Egon (Revista del CLAD Reforma y Democracia, 2018)
AbstractParticipatory budgeting emerged in Latin America, specifically in Brazil in the year 1989, expanding gradually along the continent. Its implementation has been varied in the different countries as well as in each one of them. Chilean experiences of participatory budgeting have been mostly in municipalities. More than 40 municipalities of different political affiliations developed since 2001 participatory budgets and maintained it to date. This article describes and analyzes the only case of participatory budgeting at the regional level in Chile, developed since 2014 in Los Ríos region. The paper aims to explore the institutional design and conditioning factors in its development in order to identify the factors that influence democratic processes in public investment at the regional level. As main result, as well as in the municipal experiences, the predominant factor in the origin and development of participatory budgeting is the government’s political will. However, the initial empowerment of social leaders was decisive for this participatory mechanism no to been used as a cooptation strategy or as a renewal of political clientelism at territorial level, as it has been shown in most cases of this nature both in Chile and in Latin America. The methodology applied was the study of case. The methodological proposal on categorization of “origin and conditioning factors” of the participatory budgeting elaborated by Goldfrank (2006) and Cabannes (2004) and later merged into the work of Montecinos (2012 and 2014) was take as reference.
Keywords: Citizen Participation; Participatory Budgeting; Democracy; Decentralization; Public Investment; Regions; Case Analysis; Chile